Model Business Performance, Market Share, and Customer Customer Legitimacy in Indonesian SMEs - Kuat Prabowo, Pancanto (Yayasan Ilomata, 2024)
The integrated effects of product innovation, competitive strategy, and market orientation on the market share, customer Customer Legitimacy, and business performance of small and medium-sized firms (SMEs) in Indonesia are examined in this study. 287 SMEs from a variety of industries made up the sample for the cross-sectional study. The data in this study were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings indicate that there is a positive and significant correlation between intended performance outcomes, competitive strategy, product innovation, and market orientation, according to 12 offered hypotheses. Superior SME performance is influenced by the Market Orientation Framework and the Resource-Based View (RBV) grand theory with regard to these strategic factors. The results provide guidance for strategic decision making and policy development for the Indonesian SME sector, with implications for scholars, practitioners, and policy makers.